Seeds that clean water - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1992)
Trials conducted by the Microbiology Department of the University of Leicester, UK, to decontaminate water by using seeds from the tree Moringa obleifa were reported in Spore 34 (Newslines page 11). Professor Hassan Musnad from the Forestry Research...